Research of singular spectrum analysis in the processing of meteorological measurings; Proceedings of SPIE; Vol. 11560 : Atmospheric and Ocean Optics: Atmospheric Physics - Botygin I. A. Igor Aleksandrovich; Novitskaya K. V.; Tartakovsky V. A.; Sherstnev V. S. Vladislav Stanislavovich; Sherstneva A. I. Anna Igorevna (2020, 2020)
Title screen